The measurement of the velocities of P and S waves propagating in the surface layer of ice sheet at Mizuho Station, East Antarctica - Kenji Ishizawa (National Institute of Polar Research, 1981)
The measurements of P and S wave velocity in the surface layer down to a depth of 80m were made at Mizuho Station (70°42'S, 44°20'E, 2230m a.s.l.) in 1978 by the following method : one was a borehole logging and the other was a refraction. The variation of the velocity with depth was obtained and it was found that the velocity obtained in the measurement was approximately equal to that obtained experimentally in a laboratory using the core samples drilled at Mizuho Station. The data of P wave velocity measured in Antarctica and Greenland were summarized and the relationship between the P wave velocity at a depth of 50m, V_P, and the mean annual temperature, T_m, was obtained as follows : V_P=0.034T_m+4.529(km/s).